Efforts to Increase The Creativity of Low Class Students by Using Origami Paper at State Elementary School 050696 Namu Poultry - Adinda Armania; Muhammad Iqbal (Journal of General Education Science, 2024)
This research aims to increase the creativity of lower class students at SD Negeri 050696 Namu Unggas. This research is classroom action research (PTK). This research has four steps in each cycle, consisting of planning, action, observation and reflection. This research was carried out at SD Negeri 050696 Namu Unggas for class I students, totaling 18 students consisting of 7 male students and 11 female students. This research was carried out in the odd semester of the 2023/2024 academic year. Data collection techniques are observation and assignment. Based on the results research is known to exist increase percentage from cycle I meeting 1 as much 70% Then on cycle I meeting 2 increase become 75%. On cycle II meeting 1 experienced an increase from the results of cycle I meeting 2 became 80% later increase Again on cycle II meeting 2 become 85%. Withexists enhancement the learning using origami paper give effect real to creativity Study student. Application learning with origami paper can be done increase creativity Study student . Efforts made by teachers to increase the creativity of lower class students in using origami art at SD Negeri 050696 Namu Unggas include creating comfortable learning room conditions, increasing motivation for lower class students and encouraging student creativity.